2005
DOI: 10.1111/j.1600-0420.2005.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

The cut‐and‐paste method for primary pterygium surgery: long‐term follow‐up

Abstract: ABSTRACT.Objective: To evaluate the recurrence rate, reoperation rate and side-effects of a novel technique for pterygium surgery. Design: Retrospective study. Participants: The study included 461 eyes of 381 patients operated for primary nasal pterygium by the same surgeon between 1994 and 2003 and followed for 23 ± 20 months (range 6-112 months). Methods: Autologous conjunctival grafts harvested at the superotemporal limbus were used to cover the sclera after pterygium excision. Using a retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 39 publications
6
112
2
6
Order By: Relevance
“…This effort to mask the patients was also performed in earlier studies. [5][6][7][8] When fibrin glue is used, the retraction of the host conjunctiva or graft may result in gap formation between the graft in the early post-operative period. It is suggested that rapid epithelisation of the amniotic membrane prevents post-operative inflammation and thereby reduces the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This effort to mask the patients was also performed in earlier studies. [5][6][7][8] When fibrin glue is used, the retraction of the host conjunctiva or graft may result in gap formation between the graft in the early post-operative period. It is suggested that rapid epithelisation of the amniotic membrane prevents post-operative inflammation and thereby reduces the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were also consistent with the studies of CA using fibrin glue, in which a number of different symptom scales have been used. [4][5][6][7][8] Shortening the surgery time and improving post-operative comfort may have several advantages. First, the use of fibrin glue removes the need for the tedious suturing process, the learning curve can be shortened, and better results may be more consistently achieved despite differences in surgical expertise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced recurrence rate has also been reported for conjunctival autografting in pterygium surgery with the use of fibrin glue compared with sutures. Koranyi et al postulate that fibrin glue facilitates better adhesion of the graft with the underlying tissues, which may result in early graft vascularization and thus prevents recurrence [63]. The success of autografts may also be affected by conjunctival inflammation.…”
Section: Pterygium Surgerymentioning
confidence: 99%